A membrane-targeting magnolol derivative for the treatment of methicillin-resistant Staphylococcus aureus infections - Zhang, Fushan; Fang, Hui; Zhao, Yuxin; Zhao, Buhui; Qin, Shangshang; Wang, Yu; Guo, Yong; Liu, Jifeng; Xu, Ting (Frontiers in Microbiology, 2024)
Multidrug-resistant bacterial infections are a major global health challenge, especially the emergence and rapid spread of methicillin-resistant staphylococcus aureus (MRSA) urgently require alternative treatment options. Our study has identified that a magnolol derivative 6i as a promising agent with significant antibacterial activity against S. aureus and clinical MRSA isolates (MIC = 2−8 μg/mL), showing high membrane selectivity. Unlike traditional antibiotics, 6i demonstrated rapid bactericidal efficiency and a lower propensity for inducing bacterial resistance. Compound 6i also could inhibit biofilm formation and eradicate bacteria within biofilms. Mechanistic studies further revealed that 6i could target bacterial cell membranes, disrupting the integrity of the cell membrane and leading to increased DNA leakage, resulting in potent antibacterial effects. Meanwhile, 6i also showed good plasma stability and excellent biosafety. Notably, 6i displayed good in vivo antibacterial activity in a mouse skin abscess model of MRSA-16 infection, which was comparable to the positive control vancomycin. These findings indicated that the magnolol derivative 6i possessed the potential to be a novel anti-MRSA infection agent.